Implementasi Smart Tourism dengan Teknologi Digital untuk Meningkatkan Daya Tarik dan Keberlanjutan Ekowisata pada Desa Kemutug Lor Baturaden - Maliana Puspa Arum; Paradise Paradise; Adnan Setyoko (Pusat Studi Sosial dan Pengabdian Masyarakat Fisipkum Universitas Serang Raya, 2025)
This election school activity originated from concerns about the impact of the 2020 Regional Head Elections This Community Service activity was carried out with the aim of supporting the development of ecotourism potential in Kemutug Lor Village, Baturaden District, through the implementation of a smart tourism concept based on digital technology. Partners in this activity are the administrators of the Kemutug Lor Tourism Village who have a crucial role in the management and development of nature- and culture-based tourism potential. Kemutug Lor Village has interesting natural and cultural potential, but still faces challenges in the aspects of promotion, tourism information management, and the sustainability of tourism activities. Through this program, the implementing team carried out several stages of activities, namely identifying tourism potential, socializing the concept of smart tourism, developing a digital system in the form of a smart website management, digital marketing training for tourism managers and the community, and mentoring the implementation of technology in a sustainable manner. The results of the activity showed an increase in the capacity of the tourism village administrators in utilizing technology for tourism promotion and management, as well as the formation of an integrated digital tourism information system. Thus, the implementation of smart tourism in Kemutug Lor Village was able to increase the attractiveness of the destination, expand the reach of promotions, and support the sustainability of community-based ecotourism.